Investigation of a tartaric acid-based linear polyamide and dimer as chiral selectors in liquid chromatography - Oxelbark, Joakim; Gidlund, Peter (Chirality (New York, N.Y.), 2005)
A twin selector for enantioselective liquid chromatography based on O,O′‐bis(dimethyl)benzoyl tartaric diamide was synthesized and compared to commercially available Kromasil CHI‐DMB (O,O′‐bis(dimethyl)benzoyl tartaric diamide). A linear polyamide based on the same tartaric acid derivative was also synthesized, immobilized on silica, and evaluated as stationary phase. The twin selector was immobilized as a brush‐type phase, with similar bonding chemistry as in Kromasil CHI‐DMB. It was shown to exhibit lower resolution power than Kromasil CHI‐DMB. However, retention and separation factors obtained on the respective sorbents were shown to exhibit interdependence. CD spectra of the twin selector give no indication that the respective branches interact in the solvent mixtures employed for chromatography. The linear polyamide showed lower enantioselectivity and higher retention than Kromasil CHI‐DMB. Chirality 17:79–84, 2005. © 2005 Wiley‐Liss, Inc.